Times of transition: Judea in the early Hellenistic period - Honigman, Sylvie; Nihan, Christophe; Lipshits, ʿOded (Mosaics, 2021)
The chronological frame, politics and identity -- The history of rural settlement in Judea -- The workings of empires in local and comparative perspectives -- The Pentateuch : early Greek translations and receptions -- Biblical texts in the 3rd century BCE.
"The present volume includes a collection of essays, most of which were initially presented at an international conference titled 'Judea in the Long Third Century BCE: The Transition between the Persian and Hellenistic Periods', held at the Sonia and Marco Nadler Institute of Archaeology, Tel Aviv University, from May 31 to June 3, 2014"--Preface
Includes bibliographical references and indexes
Keywords: Bible -- Old Testament -- History of Biblical events -- Congresses; Judaea (Region) -- Antiquities -- Congresses; Judaea (Region) -- History -- Congresses; Konferenzschrift -- 2014 -- Tel Aviv; Geschichte 332 v. Chr.-198 v. Chr.; Judäa